2004
DOI: 10.1103/physrevlett.93.055504
|View full text |Cite|
|
Sign up to set email alerts
|

Degradation of Boron-Doped Czochralski-Grown Silicon Solar Cells

Abstract: The formation mechanism and properties of the boron-oxygen center responsible for the degradation of Czochralski-grown Si(B) solar cells during operation is investigated using density functional calculations. We find that boron traps an oxygen dimer to form a bistable defect with a donor level in the upper half of the band gap. The activation energy for its dissociation is found to be 1.2 eV. The formation of the defect from mobile oxygen dimers, which are shown to migrate by a Bourgoin mechanism under minorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…Hence, a staggered configuration has also been proposed for the B s O 2i complex as a possible core structure. 15 Interestingly, very recent density-functional calculations 20 , the latter one being equivalent to the structure proposed before. 15 The calculations also showed that B s O 2i sq is the more stable configuration in the single positive charge state, while B s O 2i st is the more stable when neutral.…”
Section: Boron-oxygen-related Degradationmentioning
confidence: 86%
See 1 more Smart Citation
“…Hence, a staggered configuration has also been proposed for the B s O 2i complex as a possible core structure. 15 Interestingly, very recent density-functional calculations 20 , the latter one being equivalent to the structure proposed before. 15 The calculations also showed that B s O 2i sq is the more stable configuration in the single positive charge state, while B s O 2i st is the more stable when neutral.…”
Section: Boron-oxygen-related Degradationmentioning
confidence: 86%
“…15 The calculations also showed that B s O 2i sq is the more stable configuration in the single positive charge state, while B s O 2i st is the more stable when neutral. 20 The ionization energies of the B s O 2i defect were calculated using the Marker Method. 20 These calculations revealed that B s O 2i sq has in fact a (0/+) donor level in the upper half of the silicon band gap approximately between E C −0.1 eV and E C −0.3 eV, if the structure is confined to this geometry as is predicted for temperatures around room temperature, suggesting that B s O 2i sq+ is the most likely candidate for the center responsible for the solar cell degradation.…”
Section: Boron-oxygen-related Degradationmentioning
confidence: 99%
“…2 and 8) or such complex is electrically inactive. 9 In Ga and B co-doped Cz-Si samples of the same total doping 16 cm À3 , Arivanandhan et al 10 measured lower lifetime after degradation in samples containing higher [B]. This result might lead one to question Voronkov and Falster's model which would expect, in Si containing B, the amplitude of the degradation to be proportional to p 0 and independent on [B].…”
mentioning
confidence: 93%
“…[86][87][88][89] The diffusion of oxygen is mainly via O i and O 2i species as described in a recent DFT study by Timerkaeva et al 88 Regarding the O i at the ground state configuration, the O atom is bonded to two neighbouring Si atoms (Si 1 and Si 2 , refer to Fig. 4(a)) and the remaining valence electrons form two lone pairs on the O atom.…”
Section: Oxygen Diffusion Processes In Simentioning
confidence: 96%